The Olfactory Receptor Gene Product, OR5H2, Modulates Endometrial Cancer Cells Proliferation via Interaction with the IGF1 Signaling Pathway - Rand Shibel; Rive Sarfstein; Karthik Nagaraj; Lena Lapkina-Gendler; Zvi Laron; Manisha Dixit; Shoshana Yakar; Haim Werner (Cells, 2021)
Endometrial cancer is the most common gynecologic malignancy in Western countries. The insulin-like growth factor-1 (IGF1) axis has an important role in endometrial cancer biology and emerged as a promising therapeutic target in oncology. However, there is an urgent need to identify biomarkers that may help in patient stratification and prognosis. Laron syndrome (LS) is a type of dwarfism that results from the mutation of the growth hormone receptor (GHR) gene, leading to congenital IGF1 deficiency. While high circulating IGF1 is regarded as a risk factor in cancer, epidemiological studies have shown that LS patients are protected from cancer development. Recent genome-wide profilings conducted on LS-derived lymphoblastoid cells led to the identification of a series of genes whose over- or under-representation in this condition might be mechanistically linked to cancer protection. The olfactory receptor 5 subfamily H member 2 (OR5H2) was the top downregulated gene in LS, its expression level being 5.8-fold lower than in the control cells. In addition to their typical role in the olfactory epithelium, olfactory receptors (ORs) are expressed in multiple tissues and play non-classical roles in various pathologies, including cancer. The aim of our study was to investigate the regulation of OR5H2 gene expression by IGF1 in endometrial cancer. Data showed that IGF1 and insulin stimulate OR5H2 mRNA and the protein levels in uterine cancer cell lines expressing either a wild-type or a mutant p53. OR5H2 silencing led to IGF1R downregulation, with ensuing reductions in the downstream cytoplasmic mediators. In addition, OR5H2 knockdown reduced the proliferation rate and cell cycle progression. Analyses of olfr196 (the mouse orthologue of OR5H2) mRNA expression in animal models of GHR deficiency or GH overexpression corroborated the human data. In summary, OR5H2 emerged as a novel target for positive regulation by IGF1, with potential relevance in endometrial cancer.